Implementation of Affirmative Action Policies to Meet Employment Quotas for Workers with Disabilities in the Private Sector in Bogor City - Aisyah Nurhana; H. E. Rakhmat Jazuli; Ahmad Rayhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of affirmative employment policy concerning the fulfillment of disability employment quotas within the private sector in Kota Bogor and evaluates the extent to which regulatory obligations have been translated into substantive labor inclusion. Employing an empirical legal research design with a socio-legal approach, the study combines field-based evidence obtained through semi-structured interviews, institutional observation, and document analysis with qualitative legal interpretation. Primary data were collected from government officials, labor inspectors, Disability Service Unit personnel, and representatives of disability organizations, while secondary data consisted of statutory regulations, administrative records, and scholarly literature. The findings indicate that affirmative policy has been institutionally operationalized through labor information services, vocational preparation, employment facilitation, mediation mechanisms, and disability-oriented administrative support. Practical outcomes remain limited due to the persistence of profit-centered recruitment behavior among private enterprises, restricted availability of work-ready disability labor, and weak supervisory enforcement. Analysis through governmental action theory and welfare-state theory demonstrates that the legal framework has not yet generated sufficient coercive and distributive effects to ensure compliance. Strengthening regulatory supervision, institutional coordination, and labor capacity development emerges as a necessary condition for transforming formal quota obligations into effective realization of equal employment rights.